The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1080/0735648x.2005.9721206
|View full text |Cite
|
Sign up to set email alerts
|

Arrests Among Homeless and Runaway Youths: The Effects of Race and Gender

Abstract: This study examined the contributions of race and gender to the likelihood of a first post-run arrest for a more serious and less serious offense in a sample of homeless and runaway youths from four Midwestern states. Event history analysis was used to test the hypothesis that Y o d e r e t a l . i n J o u r n a l o f C r i m e a n d J u s t i C e 2 8 ( 2 0 0 5 ) 36 race and gender would interact so that the likelihood of a first post-run arrest for a more serious and less serious offense would be highest for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Younger runaways were more likely to associate with deviant peers and to report an arrest. The latter finding is supported by a marginal relationship between age at first runaway and arrest for serious offenses (Yoder et al, 2005). However, previous research found no relationship between the length of time that adolescents were living on their own and arrest (Chapple et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Younger runaways were more likely to associate with deviant peers and to report an arrest. The latter finding is supported by a marginal relationship between age at first runaway and arrest for serious offenses (Yoder et al, 2005). However, previous research found no relationship between the length of time that adolescents were living on their own and arrest (Chapple et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…By examining official arrest records, Kaufman and Spatz-Widom (1999) reported that running away multiple times prior to 15 years of age increased the odds of juvenile arrest by 3:1. The primary focus in the homeless and runaway literature has been externalizing behaviors, barring a few studies that explored criminal charges (Hagan & McCarthy, 1997), incarceration (McCarthy & Hagan, 1992a), and arrest (Chapple, Johnson, & Whitbeck, 2004;Kaufman & Spatz-Widom, 1999;Yoder, Munoz, Whitbeck, Hoyt, & McMorris, 2005). For instance, assaulting behavior (Baron & Hartnagel, 1998); deviant subsistence strategies, such as stealing, burglary, shoplifting, and prostitution to get money or food (Whitbeck & Hoyt, 1999); involvement in violent crime, drug selling, and serious theft (Hagan & McCarthy, 1997); and drug use (Chen, Tyler, Whitbeck, & Hoyt, 2004) are well-known among street youth.…”
mentioning
confidence: 99%